answersLogoWhite

0

x2 - 18x + 72 = 0

(x - 6)(x - 12) = 0

x ∈ {6, 12}

User Avatar

Wiki User

13y ago

Still curious? Ask our experts.

Chat with our AI personalities

RossRoss
Every question is just a happy little opportunity.
Chat with Ross
DevinDevin
I've poured enough drinks to know that people don't always want advice—they just want to talk.
Chat with Devin
LaoLao
The path is yours to walk; I am only here to hold up a mirror.
Chat with Lao

Add your answer:

Earn +20 pts
Q: What are the roots of the quadratic equation x2 - 18x 72 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Algebra

What are the solutions for the quadratic equation x2 minus 21x equals 72?

x2 - 21x = 72x2 - 21x - 72 = 0(x - 24) (x + 3) = 0x = 24x = -3


What is the equation of 72 in 6?

As an equation if: 6x = 72 then x = 12


Factor 2x squared plus 6x - 8 equals 72?

2x2 + 6x - 8 = 72 ∴ 2x2 + 6x + 64 =0 ∴ x2 + 3x + 32 = 0 This can not be factored, as x is not equal to any integer. Using the quadratic equation, we find that: x = -3/2 ± √119 / 2i


What is x2-72x-735 factored?

I assume you mean; X^2 - 72X - 735 = 0 The only way I would do this is by the quadratic formula discriminant (-72)^2 - 4(1)(-735) = 8124 and means two real roots X = - b (+/-) sqrt(b^2-4ac)/2a a = 1 b = - 72 c = - 735 X = - (-72) (+/-) sqrt[(-72)^2 - 4(1)(-735)]/2(1) X = 72 (+/-) sqrt(8124)/2 X = [72 (+/-) 2sqrt(2031)]/2 Ugly, but true.


What is the new Transforming Method to solve quadratic equation?

Solving quadratic equations by the new Transforming Method. It proceeds through 3 Steps. STEP 1. Transform the equation type ax^2 + bx + c = 0 (1) into the simplified type x^2 + bx + a*c = 0 (2), with a = 1, and with C = a*c. STEP 2. Solve the transformed equation (2) by the Diagonal Sum Method that immediately obtains the 2 real roots y1, and y2. STEP 3. Divide both y1, and y2 by the coefficient a to get the 2 real roots of the original equation (1): x1 = y1 /a, and x2 = y2/a. Example 1. Solve: 12x^2 + 5x - 72 = 0 (1). Solve the transformed equation: x^2 + 5x - 864 = 0. Roots have different signs (Rule of Signs). Compose factor pairs of a*c = -864 with all first numbers being negative. Start composing from the middle of the factor chain to save time. Proceeding:.....(-18, 48)(-24, 36)(-32, 27). This last sum is -32 + 27 = -5 = -b. Then, the 2 real roots of (2) are: y1 = -32, and y2 = 27. Back to the original equation (1), the 2 real roots are: x1 = y1/a = -32/12 = -8/3, and x2 = y2/a = 27/12 = 9/4. Example 2. Solve 24x^2 + 59x + 36 = 0 (1). Solve the transformed equation x^2 + 59x + 864 = 0 (2). Both roots are negative. Compose factor pairs of a*c = 864 with all negative numbers. To save time, start composing from the middle of the factor chain. Proceeding:....(-18, -48)(-24, -36)(-32, -27). This last sum is -59 = -b. Then 2 real roots of equation (2) are: y1 = -32 and y2 = -27. Back to the original equation (1), the 2 real roots are: x1 = y1/24 = -32/24 = -4/3, and x2 = y2/24 = -27/24 = -9/8. To know how does this new method work, please read the article titled: "Solving quadratic equations by the new Transforming Method" in related links.